The Application Study in Solar Energy Technology for Highway Service Area: A Case Study of West Lushan Highway Low-Carbon Service Area in China - Xiaochun Qin; Yi Shen; Shegang Shao (International Journal of Photoenergy)
A lot of research works have been made concerning highway service area or solar technology and acquired great achievements. However, unfortunately, few works have been made combining the two topics together of highway service areas and solar energy saving to make a systemic research on solar technology application for highway service area. In this paper, taking West Lushan highway low-carbon service area in Jiangxi Province of China as the case study, the advantages, technical principles, and application methods of solar energy technology for highway service area including solar photoelectric technology and solar water heating technology were discussed based on the analysis of characteristics of highway low-carbon service area; the system types, operation mode, and installing tilt angle of the two kinds of solar systems suitable for highway service areas were confirmed. It was proved that the reduction of the cost by electricity savings of solar system was huge. Taking the investment of the solar systems into account, the payback period of solar photoelectric systems and solar water heating systems was calculated. The economic effect of the solar systems in West Lushan highway service area during the effective operation periods was also calculated and proved very considerable.